The Factors That Influence Consumer Decisions in Purchasing Products in Alfamart Minimarket in Pinang, a Subdistrict of Tangerang - Nawawi, Muhammad Tony; Ikhaz, Muhammad Safiqi (Bina Nusantara University, 2015)
This study analyzes the factors that influence consumer decisions in purchasing products in Alfamart minimarket in Pinang, a subdistrict of Tangerang. The population in this study is the consumers of householdproducts that is retailed in minimarket Alfamart. The sampling technique used is purposive random sampling and samples are taken from 200 consumers. The purpose of the study is to examine and analyze the factors that may affect consumers decisions in purchasing products on Alfamart mini market. The method of analysis is multiple regression analysis and assumptions test. The validity and reliability test is done by using the help ofSPSS (Statistical Program for Society Science) versus16:00. The analysis shows that all positive significant factors affect consumers decisions in purchasing products and it is evidenced by the significance 0.000<0.05,and the factor of location has no significance as evidenced by the significance value 0.478>0.05 and the value of R Square value 0.369, it means that it is only 36.9% of consumer decisions are influenced by factors of locations.